10N‐Nonyl acridine orange interacts with cardiolipin and allows the quantification of this phospholipid in isolated mitochondria - PETIT, Jean‐Michel; MAFTAH, Abderrahman; RATINAUD, Marie‐Hélène; JULIEN, Raymond (European journal of biochemistry, 1992)
The acridine orange derivative, 10N‐nonyl acridine orange, is an appropriate marker of the inner mitochondrial membrane in whole cells. We use membrane model systems to demonstrate that 10N‐nonyl acridine orange binds to negatively charged phospholipids (cardiolipin, phosphatidylinositol and phosphatidylserine). The stoichiometry has been found to be 2 mol 10N‐nonyl acridine orange/mol cardiolipin and 1 mol dye/mol phosphatidylserine or phosphatidylinositol, while, with zwitterionic phospholipids, significant binding could not be detected. The affinity constants were 2 × 106 M−1 for cardiolipin‐10N‐nonyl‐acridine‐orange association and only 7 × 104 M−1 for that of phosphatidylserine and phosphatidylinositol association. The high affinity of the dye for cardiolipin may be explained by two essential interactions; firstly an electrostatic interaction between the quaternary ammonium of nonyl acridine orange and the ionized phosphate residues of cardiolipin and secondly, hydrophobic interactions between adjacent chromophores. A linear relationship was demonstrated between the cardiolipin content of model membranes and the incorporated dye. Consequently, a convenient and rapid method for cardiolipin quantification in membranes was established and applied to the cardiolipin‐containing organelle, the mitochondrion.